A new species of Prosopistoma Latreille, 1833 (Ephemeroptera: Prosopistomatidae) from South India - Balachandran, Chellapandian; Anbalagan, Sankarappan; Kannan, Mani; Dinakaran, Sundaram; Krishnan, Muthukalingan (Zootaxa, 2016)
A new species of Prosopistoma (Ephemeroptera: Prosopistomatidae) is described on the basis of mature nymphs from Coorg, Karnataka, South India. Prosopistoma coorgum, new species can be readily distinguished from the other members of Prosopistoma by the following combination of characters: inner margin of outer canine near apex with 2–3 short spines, the length ratio of maxillary palp segments (3.3:4.8:1), ventral margin of fore tibia with 6–8 pectinate setae, and gill II leaf-like and cleft.